2022
DOI: 10.3389/fcvm.2022.903307
|View full text |Cite
|
Sign up to set email alerts
|

Correlation Between Non-insulin-Based Insulin Resistance Indices and Increased Arterial Stiffness Measured by the Cardio–Ankle Vascular Index in Non-hypertensive Chinese Subjects: A Cross-Sectional Study

Abstract: Data are limited on the relationship between the cardio–ankle vascular index (CAVI) and non-insulin-based insulin resistance (IR) indices, including the triglyceride to high-density lipoprotein cholesterol ratio (TG/HDL-C), fasting triglyceride and glucose index (TyG), and metabolic score for IR (METS-IR). In this study, we explored the relationship between TG/HDL-C, TyG, METS-IR, and the risk of increased arterial stiffness (CAVI ≥ 8.0) and compared their ability to detect arterial stiffness in the non-hypert… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3

Citation Types

0
12
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 9 publications
(14 citation statements)
references
References 33 publications
0
12
0
Order By: Relevance
“…1 ) [ 11 , 22 26 ]. Finally, ten cohort studies[ 14 , 27 35 ] and sixteen cross-sectional [ 9 , 15 , 36 49 ] studies were included in the present research, while the detailed reasons for the excluded articles are listed in Additional file 1 : Table S3.
Fig.
…”
Section: Resultsmentioning
confidence: 99%
See 2 more Smart Citations
“…1 ) [ 11 , 22 26 ]. Finally, ten cohort studies[ 14 , 27 35 ] and sixteen cross-sectional [ 9 , 15 , 36 49 ] studies were included in the present research, while the detailed reasons for the excluded articles are listed in Additional file 1 : Table S3.
Fig.
…”
Section: Resultsmentioning
confidence: 99%
“…Table 1 presents the baseline characteristics of the included studies, which were published between 2017 and 2022, with a sample size ranging from 180 to 13,706 and a total of 87,307 participants. Among the included studies, 15 were from China[ 9 , 14 , 15 , 28 , 29 , 31 , 33 , 34 , 36 , 40 , 42 , 44 , 45 , 47 , 50 ], seven were conducted in Korea [ 27 , 30 , 34 , 35 , 37 39 ], three were from [ 42 , 48 , 49 ] Japan [ 41 , 47 , 49 ], and only one originated in non-Asia (United States) [ 43 ]. The mean age of participants ranged from 28.7 to 75 years, and the BMI ranged from 22.5 to 28.5 kg/m 2 .…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…METS-IR is associated with prehypertension, hypertension, arterial stiffness, and incident ischemic heart disease. [5][6][7][8][9][10] A recent study reported the dose-response association of METS-IR with new-onset NAFLD in a non-obese Chinese population. 11 The risk of incident NAFLD increased progressively with the METS-IR (Q1: reference; Q2: hazard ratio [HR] = 2.69, 95% confidence interval [CI] = 1.87-3.86; Q3: HR = 4.25, 95% CI = 2.86-6.30; Q4: HR = 6.40, 95% CI = 4.06-10.08, P < 0.001).…”
mentioning
confidence: 99%
“…Even without circulating insulin levels in the equation, it can be validated using the euglycemic-hyperinsulinemic clamp data, frequently sampled in intravenous glucose tolerance test data, and a large cohort against the HOMA-IR. METS-IR is associated with prehypertension, hypertension, arterial stiffness, and incident ischemic heart disease [ 5 - 10 ]. A recent study reported the dose-response association of METS-IR with new-onset NAFLD in the non-obese Chinese population [ 11 ].…”
mentioning
confidence: 99%